2006
DOI: 10.1089/lap.2006.16.626
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Treatment of Simultaneously Occurring Morgagni and Paraesophageal Hernias

Abstract: A paraesophageal hernia was diagnosed in a 67-year-old female patient suffering from epigastric pain and gastroesophageal reflux disease. The patient underwent laparoscopy. Beside the paraesophageal hernia, a Morgagni hernia was also observed, with a significant part of the omentum herniated in the sac. A 360-degree Nissen fundoplication was performed, the Morgagni hernia sac was not resected, and its closure was performed with interrupted sutures. No complications were observed in the postoperative period and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Simultaneously occurring Morgagni and paraesophageal hernias is extremely rare with only two cases reported laparoscopic repair in English literature (Table 1). 4,5) There is a common belief that MH is usually asymptomatic, thus often discovered accidentally. However, in a review of 298 cases of adult MHs, Horton et al found 72% of patients presented with pain and pulmonary complaints directly related to their MHs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simultaneously occurring Morgagni and paraesophageal hernias is extremely rare with only two cases reported laparoscopic repair in English literature (Table 1). 4,5) There is a common belief that MH is usually asymptomatic, thus often discovered accidentally. However, in a review of 298 cases of adult MHs, Horton et al found 72% of patients presented with pain and pulmonary complaints directly related to their MHs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Compared with traditional open surgical techniques, laparoscopic operation has become the main method to repair both MH and paraesophageal hernia, with the advantage of minimal invasiveness and fewer complications. The abdominal approach can provide excellent exposure to allow full exploration of the hernia sac and bilateral diaphragm, provide easier access when narrowing the hernia defect, and allow for simultaneously performing other procedures such as fundoplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paraesophageal hiatal hernias account for approximately 14% of hiatal hernias and occur most commonly in adults [ 3 ]. The defect is situated anterior to esophagus and may cause characteristic symptoms of chest pain, dysphagia, regurgitation, and occult bleeding [ 2 ]. Herniation of abdominal contents into the thorax via a subcostosternal defect, as first described by Morgagni in 1769, is a congenital problem that rarely presents in adults and accounts for 3–5% of diaphragmatic hernias [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%